Fixam IT - Yudha Dirgantara; Rikha Lutfiati; Fitri Anggraeni; Wasis Haryono (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
In the current era of globalization and technological advancement in business, information systems play a critical role in driving organizational growth. A company’s success heavily relies on an efficient information system capable of providing accurate, timely, and relevant information. This study aims to design a web-based asset management information system to enhance asset management efficiency at PT Wisessa Consulting Indonesia. Asset management is a vital function that must be carried out to monitor the condition and status of assets. The main problems identified include the lack of integration in asset recording and the absence of a user access control system differentiated by role. The system development follows the Waterfall model, which consists of requirements analysis, system design, implementation, testing, and maintenance phases. The developed system manages detailed asset master data, schedules asset maintenance, and regulates user access rights based on roles—namely admin, IT support admin, IT support, manager, and branch user. The implementation results indicate that the system facilitates more accurate and structured asset recording, monitoring, and reporting processes. Furthermore, the system improves asset management effectiveness, ensures data transparency, reduces errors from manual processes, and supports data-driven strategic decision-making within the organization.